Integrated participatory commitment in university archives for accountability through digital archives - Kuswantoro, Agung; Wirawan, Arif Wahyu; Murtadlo, Muhamad Nukha (Record and Library Journal, 2025)
Background of the study: Archiving and document management are essential for ensuring the continuity of university administration. With advances in information technology, conventional archiving systems are increasingly seen as less effective and less efficient. Purpose: This study aims to assess the effectiveness of the Integrated Digital Archiving System in enhancing document management at Universitas Negeri Semarang (UNNES). Method: This research employs a quantitative approach. Data were collected through questionnaires distributed to archivists and system users at UNNES. The data provide insight into staff perceptions of document management, their expectations for the current system under development, and their feedback after testing the newly developed system. Findings: The results indicate that the MyUNNES-Siradi application and participatory commitment can explain 82.5% of the variance in document management accountability among archival staff. The partial determination coefficients show that the MyUNNES-Siradi application accounts for 51.7%, while participatory commitment accounts for 58.8%. Additionally, 85% of respondents reported high satisfaction with the system’s features, particularly the reduced time required to access and manage documents. Conclusion: Overall, the findings suggest that the digital archive system effectively improves document management at UNNES. Further development is recommended to address remaining challenges and enhance system performance.